Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1477-7827-11-65
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of oviposition and hormonal and gene regulation of ovarian follicle development in Magang geese

Abstract: BackgroundEgg laying in Magang geese is characterized by extended interruption between clutches and lowing laying rate. Both the ovarian follicular development and ovulation characteristics, and the associated endocrine and molecular regulatory mechanisms involved are poorly understood, but could be important for guiding development of molecule aided selection of egg laying performances in geese. This study, therefore, recorded egg-laying characteristics of Magang geese, and the endocrine and molecular regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Also, the hormones, such as progesterone and estradiol function in regulating the development of follicles, ovulation, and sexual behaviors in birds28 and the altered levels of reproductive hormones are associated with broodiness7. In this study, we demonstrated that progesterone and estradiol increased and the expressions of hormone-related genes were altered in the broody follicles.…”
Section: Discussionmentioning
confidence: 50%
“…Also, the hormones, such as progesterone and estradiol function in regulating the development of follicles, ovulation, and sexual behaviors in birds28 and the altered levels of reproductive hormones are associated with broodiness7. In this study, we demonstrated that progesterone and estradiol increased and the expressions of hormone-related genes were altered in the broody follicles.…”
Section: Discussionmentioning
confidence: 50%
“…Thirdly, during the postovulatory period, the recruitment of smaller follicles is suppressed by the additively‐increasing negative signal from dominant follicles in the hierarchy (Williams, ). This inhibitory signal is thought to be mediated by inhibin and follistatin proteins (Qin et al., ). Hence, it is likely that in species with a slower pace of life, in contrast to those with a faster one, IGF‐1 has a modulatory effect on activin, inhibin, and follistatin secretion, which prioritizes the proportional investment of females into each egg, presumably resulting in the development of higher‐quality offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Studies highlighted many hormones, growth factor and cytokines in the ovary playing crucial roles in the follicular development. The follicles grow and develop orderly under the control of endocrine hormone (69,70), growth factor precisely produced at different time points (71,72) and the cytokines associated with the development of follicles include TNF-α, IL1β, and interferon-γ (73)(74)(75). The impact of adiposity has been involved in troubles of female reproduction (1).…”
Section: Discussionmentioning
confidence: 99%